Chemical Composition and Nutritional Value of Different Seaweeds from the West Algerian Coast. Issue 1 (2nd January 2020) - Oucif, Hanane; Benaissa, Miloud; Ali Mehidi, Smaïl; Prego, Ricardo; Aubourg, Santiago P.; Abi-Ayad, Sidi-Mohammed El-Amine
ABSTRACT: Analysis of proximate composition, lipid fraction (fatty acids and lipid classes), macroelements, and trace elements was carried out on brown ( Cystoseira stricta; Cystoseira compressa ), red ( Corallina elongata ), and green ( Enteromorpha compressa; Ulva lactuca ) seaweeds collected from the west Algerian coast to assess their nutritional value. Protein, lipid, carbohydrate, and ash content (g kg −1 dry alga) was in the ranges 58.5–141.4, 6.4–27.1, 134.0–461.1, and 246.1–764.2, respectively. The lowest caloric value was obtained for C. elongata (827.6 kcal kg −1 dry alga); the remaining values being in the range 2, 106–2, 479 kcal kg −1 dry alga. C. elongata and C. stricta provided the highest polyunsaturated fatty acid content, while a valuable n -6/ n -3 ratio of between 0.95 and 4.20 was obtained for all species. α -Tocopherol was present in all seaweeds; the highest level was obtained in U. lactuca . Macroelements K and Na were predominant in C. compressa and C. stricta ; while Mg and Ca were most abundant in E. compressa and C. elongata, respectively. In all cases, a healthy Na/K value < 0.7 was observed, and a profitable ion quotient ratio was observed in all cases, except for C. elongata . Estimated daily intake of most minerals from the algae studied is lower than the corresponding recommended daily intake.